Implementation of Sustainable Technologies for Smart Water Resource Management: A Review (International Journal of Environmental Sciences, 2025)
Abstract: Water is an essential human requirement in all economic activities. Agriculture, renewable energy, manufacturing, and mining are all vital economic sectors. Water resources are experiencing significant pressure as population growth escalates the demand for water from competing economic sectors. Groundwater resources are being exhausted in numerous regions, jeopardizing the current and future generation’s ability to safeguard against escalating climatic variability. Consequently, information technology approaches and internet communication technologies are essential in managing water resources to mitigate the excessive wastage of freshwater and to regulate and monitor water contamination. This paper reviews research utilizing the Internet of Things as a communication platform to manage water conservation and prevent waste by homeowners and farmers. Recent advancements in information and communication technology and the Internet of Things have created new possibilities for the real-time monitoring and management of urban buildings, infrastructures, and services. This review paper seeks to offer a contemporary and insightful perspective for academics, consumers, and stakeholders about the implementation of smart and sustainable technologies in water resource management.